Niat Perilaku Generasi Z dan Milenial dalam Menggunakan Fitur Pay Later - Suparman, Michelle (Penerbit Goodwood, 2023)
Purpose: The purpose of this research was to understand why Generation Z and Millennials in Indonesia really like using PayLater by applying the Technology Acceptance Model (TAM) theory. Research Methodology: This research is a quantitative research that applies questionnaires using Google Form to 103 respondents with research subjects were Generation Z (1997 – 2012) and Millennials (1981 – 1996) in Indonesia. Random sampling was used for the sample collection. Data processing and data analysis from this research used SPSS (Statistical Package for the Social Sciences) tools and non-comparative techniques, namely, the Likert scale. Results: The results show that perceptions of usefulness, ease of use, security, and trust have a positive and significant effect on intention to use. Limitations: Educational games about natural disasters in Indonesia, including floods, landslides, earthquakes, tsunamis, volcanic eruptions, and tornadoes, including an introduction to natural disasters in Indonesia, the pre-disaster phase, and the emergency response phase. Contribution: This Research can be a good knowledge of PayLater feature providers (companies), which can provide information about consumer perceptions regarding their intention to use the PayLater feature. This information will be useful for product development. Furthermore, this research can provide valuable knowledge to understand one of the digital business features that is currently very popular, namely, PayLater. Finally, this research is good as a reference for developing or compiling research related to paylater features.